N. BALTZWER Y M. STIERLI (eds.) - Before publication. Montage in Art, Architecture and Book Design - Esteban Maluenda, Ana (ZARCH, 2017)
Nanni Baltwer Y Martino Stierli (eds.)Before publication. Montage in Art, Architecture and Book DesignPark Books, Zúrich, 2016, 144 páginas.Idioma: inglés. Tapa blanda. 38 €. ISBN 10: 3038600229. ISBN 13: 9783038600220